Potensi Kecerdasan Linguistik pada Anak Usia Dini melalui Mendongeng Di Rumah Baca Madina Kota Metro - Uswatun Hasanah; Durotun Nasyikhah; Umi Saidah Khoiriah (Universitas Al-Hikmah Indonesia, 2019)
The Children have linguistic intelligence in a great ways. During childhood, from birth to 6th years old, the children never learn vocabulary specifically. When teachers tell stories, children will gradually play important games and not only in developing interest and reading habits, but also in developing children's language and thoughts. Early childhood is a great imitator, whatever we say and do will be attached to the child, so we as adults must be able to control our speech and behavior in front of early childhood, because that will have an effect in the future. One method that can be used in developing aspects of children's language is the storytelling method.